Overview of research progress on the association of dietary potassium intake with serum potassium and survival in hemodialysis patients, does dietary potassium restriction really benefit hemodialysis patients? - Sun, Zuoya; Jiao, Jian; Lu, Gang; Liu, Ruihong; Li, Zhuo; Sun, Yi; Chen, Zhiyuan (Frontiers in Endocrinology, 2023)
For the general population, increasing potassium intake can reduce the incidence of cardiovascular and cerebrovascular diseases. However, since hyperkalemia is a common and life-threatening complication in maintenance hemodialysis patients, which can increase the risk of malignant arrhythmia and sudden death, the current mainstream of management for hemodialysis patients is dietary potassium restriction in order to prevent hyperkalemia. Hemodialysis patients are usually advised to reduce dietary potassium intake and limit potassium-rich fruits and vegetables, but there is limited evidence to support this approach can reduce mortality and improve quality of life. There is still no consistent conclusion on the association between dietary potassium intake and serum potassium and survival in hemodialysis patients. According to the current small observational studies, there was little or even no association between dietary potassium intake and serum potassium in hemodialysis patients when assurance of adequate dialysis and specific dietary patterns (such as the plant-based diet mentioned in the article) are being followed, and excessive dietary potassium restriction may not benefit the survival of hemodialysis patients. Additionally, when assessing the effect of diet on serum potassium, researchers should not only focus on the potassium content of foods, but also consider the type of food and the content of other nutrients. However, more large-scale, multi-center clinical trials are required to provide high-quality evidence support.Besides, further research is also needed to determine the optimal daily potassium intake and beneficial dietary patterns for hemodialysis patients.